Proteção de sobrecorrente direcional aplicada a linhas de transmissão - Silva, João Paulo da (2019)
The present work presents the study, elaboration of an algorithm and the implementation of a directional overcurrent relay in a transmission line. The electrical system used was modeled and simulated in the ATPDraw sottware and its voltage and current data were used in the Matlab Software for validation of the study. The Fourier Discrete Transform was used to extract the fundamental component of the voltage and current phasors, calculating the positive and negative sequence and voltage currents to detect faults applied in the study system. By means of the simulated faults in the electric power system used, a methodology was implemented where it monitors overcurrent in a previously established direction. In order to carry out a rear protection with the detected faults, the overcurrent elements of the instant and timed, phase and neutral units were adjusted, thus ensuring, coordinated performance of these protections, and incorporating, selectivity, speed of operation and reliability in the electrical system where was implemented. The elaborated algorithm obtained a behavior within the expected three - phase, biphasic and simulated monophasic faults with a percentage of 92% of correct answers, thus validating the study and proposed method.